2002
DOI: 10.1016/s0165-0378(01)00086-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of peri-attachment embryo development in the golden hamster: role of growth factors

Abstract: The molecular regulation of mammalian peri-implantation development is complex and difficult to study in vivo. We successfully cultured hamster blastocysts through hatching and peri-attachment stages, using a chemically defined medium, HECM-2h. Using this system, we showed that a species-specific, embryonic cysteine-like protease is involved in blastocyst hatching and that the process is modulated by growth factors. In particular, heparin binding-epidermal growth factor (HB-EGF) or leukemia inhibitory factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…To date, the mechanism of implantation remains elusive, although mounting evidence suggests a complex and coordinated series of events leading to consensual interaction between the endometrium and the embryo; especially, growth factor and cell adhesion molecule interactions were thought to be important. Several previous reports indicated that addition of HB-EGF to growth media significantly improved development of mouse (3), hamster (18) and human (19) embryos to the expanded blastocyst stage, and significantly promoted hatching in a dosedependent manner. Similarly, our results show that addition of HB-EGF to the media improved embryo development and hatching rate.…”
Section: Discussionmentioning
confidence: 92%
“…To date, the mechanism of implantation remains elusive, although mounting evidence suggests a complex and coordinated series of events leading to consensual interaction between the endometrium and the embryo; especially, growth factor and cell adhesion molecule interactions were thought to be important. Several previous reports indicated that addition of HB-EGF to growth media significantly improved development of mouse (3), hamster (18) and human (19) embryos to the expanded blastocyst stage, and significantly promoted hatching in a dosedependent manner. Similarly, our results show that addition of HB-EGF to the media improved embryo development and hatching rate.…”
Section: Discussionmentioning
confidence: 92%
“…It has been described that cocultured cells release a complex mixture of many different growth factors into the embryo culture media, which is believed to be the primary reason behind the improved embryonic development associated with coculture (Richter 2008). In the reproductive tract the preimplantation embryos develop in the absence of direct cell contact in a free-floating way, nevertheless they are dependent on released factors by oviduct, uterus luminal and by themselves (Besenfelder et al 2012; Mishra and Seshagiri 2000; Seshagiri et al 2002), including factors as IGF-I and -II, TGFα, TGFβ, IL-1b, EGF, SCF and LIF among others (Hardy and Spanos 2002). It is well known that both MSC and MEF cells release bioactive factors supporting embryonic growth and it is likely that these factors positively impacted early embryo development as shown here.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous application of recombinant HBEGF matures rodent blastocysts in vitro, augmenting their ability to hatch from the zona pellucida, and accelerating trophoblast differentiation and adhesion competency (Das et al, 1994b; Wang et al, 2000). HBEGF increases the rate of hamster blastocyst hatching, adhesion competency, and trophoblast outgrowth (Mishra and Seshagiri, 2000; Seshagiri et al, 2002) and augments development of 8-cell rat embryos to the blastocyst stage (Tamada et al, 1999). Intraluminal injection of HBEGF induces implantation of rat embryos in a delayed implantation model (Tamada et al, 1999).…”
Section: The Role Of Hbegf At Implantationmentioning
confidence: 99%